Penerapan Metode Teams Games Tournament (TGT) untuk Meningkatkan Keaktifan Siswa Kelas VIII pada Pelajaran Biologi di Sekolah Kristen ABC Karawaci [The Implementation of a Teams Games Tournament to Increase Students' Activeness in a Grade VIII Biology Class at a Christian School in Karawaci] - Alan Angelina Tonapa; Siane Indriani; Destya Waty Silalahi (Universitas Pelita Harapan, 2016)
Based on observing grade VIII students, the researcher found that the students were passive during the learning process when it came to sharing ideas or opinions, asking and answering questions, and solving problems given by the teacher. The researcher decided to implement the TGT cooperative learning method in order to solve the problem. It was expected that through the implementation of this method, the students' activeness would increase. Observation was also used to discover which steps of the TGT method might increase a student’s activeness. The research was conducted on October 28, 2015 and October 29, 2015, with 22 students as the subjects using the Class Action Research Method. Data was collected and analyzed by using student’s activeness observation sheets, TGT’s implementation observation sheets, the researcher’s reflection journal, student’s questionnaire sheets, and mentor’s feedback. Based on the data analysis from those instruments, it can be concluded that the students' activeness increases by implementing the TGT method. The steps of the TGT method implemented consisted of class preparation, learning in study groups, games and tournaments, and team recognition and these increased students' activeness in learning Biology.BAHASA INDONESIA ABSTRAK: Berdasarkan observasi di kelas VIII, peneliti menemukan masalah bahwa siswa-siswa pasif selama pembelajaran misalnya dalam mengemukakan ide atau pendapat, bertanya dan menjawab pertanyaan guru, serta mengerjakan soal yang diberikan oleh guru. Maka, peneliti memutuskan untuk menerapkan metode TGT dalam mengatasi permasalahan tersebut. Diharapkan melalui penerapan metode ini, tujuan peneliti dapat tercapai, yaitu meningkatkan keaktifan siswa melalui penerapan metode TGT dan mengetahui langkah-langkah penerapan metode TGT dalam peningkatan keaktifan siswa. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) pada tanggal 28 dan 29 Oktober 2015 dengan subjek 22 siswa. Pengumpulan data dilakukan dengan menggunakan instrumen lembar observasi keaktifan siswa, lembar observasi penerapan TGT, jurnal refleksi peneliti, lembar angket siswa, dan umpan balik mentor. Berdasarkan analisis data dari berbagai instrumen tersebut, maka keaktifan siswa meningkat dengan diterapkannya metode TGT dan selama penerapansetiap tahapan TGT yang terdiri dari tahap penyajian kelas, tahap belajar dalam kelompok, tahap permainan turnamen, dan tahap penghargaan kelompok dapat meningkatkan keaktifan siswa pada pelajaran Biologi.